Whither Diversion or Broadening the Bargaining Space: Why Africa Needs New Non-traditional Partners in Development Cooperation - Mudzengerere, Armstrong (Africana Studia, 2023)
Africa needs new non-conventional partners like Vietnam and the United Arab Emirates in Development Cooperation (DC). Existing studies have focused more on conceptual dissections of strategies towards Africa in the trendy Africa+1 summit binge overlooking the lessons and complementarities that can emerge from reciprocal direct cooperation between African countries and new non-traditional partners. The paper suggests that the United Arab Emirates (UAE) and Vietnam are offering opportunities for shared learning, technology transfer, information sharing and “learning by doing together” in agriculture transformation and digitalization for intra Africa trade. In proposing this avenue of thought for new nontraditional partners, the paper seeks to recenter the discourse on the specific investment needs of Africa, “putting money where Africa needs it”. Keywords: Vietnam, United Arab Emirates (UAE), development cooperation, South-South cooperation.